Evaluation focused on learning: a way to innovate in Higher Education Institutions (2019)
The following text is a research chapter which presents the state of the art of the investigation Prácticas y experiencias de la evaluación del aprendizaje en la Universidad Sergio Arboleda, which aims to propose an evaluation model focused on learning. This document presents the project carried out by the INVEDUSA group at the Sergio Arboleda University: the theoretical references that are the basis of this research and which are related to traditional and continuous evaluation; the evaluation and its didactic resources; the student as the main subject of knowledge and evaluative diversity. Each of these provides theoretical and conceptual elements for the development of the research in progress.